Stereological estimation of total cell numbers in the human cerebral and cerebellar cortex - Walløe, Solveig; Pakkenberg, Bente; Fabricius, Katrine (Frontiers in Human Neuroscience, 2014)
Our knowledge of the relationship between brain structure and cognitive function is still limited. Human brains and individual cortical areas vary considerably in size and shape. Studies of brain cell numbers have historically been based on biased methods, which did not always result in correct estimates and were often very time-consuming. Within the last 20–30 years, it has become possible to rely on more advanced and unbiased methods. These methods have provided us with information about fetal brain development, differences in cell numbers between men and women, the effect of age on selected brain cell populations, and disease-related changes associated with a loss of function. In that this article concerns normal brain rather than brain disorders, it focuses on normal brain development in humans and age related changes in terms of cell numbers. For comparative purposes a few examples of neocortical neuron number in other mammals are also presented.